Respuesta :
(A)
Evaluate [tex]p[/tex] and [tex]q[/tex] at the given values of [tex]t[/tex], then plug them into the inner product:
[tex]p(t)=3t-t^2\implies\begin{cases}p(-1)=-4\\p(0)=0\\p(1)=2\end{cases}[/tex]
[tex]q(t)=3+2t^2\implies\begin{cases}q(-1)=5\\q(0)=3\\q(1)=5\end{cases}[/tex]
Now,
[tex]\langle p,q\rangle=4\cdot5+0\cdot3+2\cdot5=30[/tex]
[tex]\|p\|=\sqrt{\langle p,p\rangle}=(-4)^2+0^2+2^2=20[/tex]
[tex]\|q\|=\sqrt{\langle q,q\rangle}=5^2+3^2+5^2=59[/tex]
(B)
Let [tex]V[/tex] denote the subspace spanned by [tex]p[/tex]. We need an orthonormal basis for [tex]V[/tex]. Since
[tex]p(t)=3t-t^2=3\cdot t+(-1)\cdot t^2[/tex]
we have the basis vectors [tex]\{t,t^2\}[/tex]; normalize these vectors to get the orthonormal basis,
[tex]\left\{\dfrac t{|t|},\dfrac{t^2}{|t^2|}\right\}=\left\{\dfrac t{|t|},1\right\}[/tex]
Then the projection of [tex]q[/tex] onto [tex]V[/tex] is
[tex]\mathrm{proj}_Vq(t)=\left(q(t)\cdot\dfrac t{|t|}\right)\dfrac t{|t|}+\left(q(t)\cdot1\right)1[/tex]
[tex]\mahtrm{proj}_Vq(t)=\dfrac{3t^2+2t^4}{t^2}+(3+2t^2)=\boxed{6+4t^2}[/tex]
A).
[tex]< p, q >=-10\\||p||=9\sqrt{2} \\||q||=3\sqrt{2}[/tex]
B).The orthogonal projection of q onto the subspace spanned by p is[tex]proj_vq(t)=6+4t^2[/tex]
We have [tex]p(t) = 3t - t^2 ,q(t) = 3 + 2t^2[/tex]
And < p, q >= p(−1)q(−1) + p(0)q(0) + p(1)q(1).
Now,
A).
[tex]p(-1) = 3.(-1) - (-1)^2 \\=-4\\p(1)=3.1-1^2\\=2q(-1) = 3 + 2.(-1)^2\\=5\\q(1) = 3 + 2.(1)^2\\=5p(0) = 3.0 - 0^2 \\=0\\q(0) = 3 + 2.0^2\\=3\\< p, q >= p(-1)q(-1) + p(0)q(0) + p(1)q(1)\\< p, q >=-4.5+0.3+2.5\\=-10\\||p||=<p,p>\\=\sqrt{(-4)^2+0+2^2} \\=\sqrt{20} \\=2\sqrt{5} \\||q||=<q,q>\\=\sqrt{5^2+3^2+5^2} \\=\sqrt{59}[/tex]
B)Let V be the subspace spanned by p.
Now, an orthonormal basis for p is[tex](t,t^2)[/tex]
Then the projection of q onto the subspace spanned by p is
[tex]proj_vq(t)=(q(t).\frac{t}{|t|} ).\frac{t}{|t|} +(q(t).1)1\\proj_vq(t)=\frac{3t^2+2t^4}{t^2} +(3+2t^2)\\proj_vq(t)=6+4t^2[/tex]
Learn more:https://brainly.com/question/13012535